Optimal timing of coronary intervention in patients resuscitated from cardiac arrest without ST-segment elevation myocardial infarction (NSTEMI): A systematic review and meta-analysis. (November 2019) - Barbarawi, Mahmoud; Zayed, Yazan; Kheiri, Babikir; Barbarawi, Owais; Al-Abdouh, Ahmad; Dhillon, Harsukh; Rizk, Fatima; Bachuwa, Ghassan; Alkotob, Mohammad L.
Abstract: Objective: Performing immediate coronary angiography (CAG) in patients with a cardiac arrest and a non-ST-elevation myocardial infarction (NSTEMI) remains a highly debated topic. We performed a meta-analysis aiming to evaluate the influence of immediate, delayed, and no CAG in patients with cardiac arrest and NSTEMI. Methods: A comprehensive literature review of Pubmed/MEDLINE, Cochrane Library, and Embase was performed for all studies that compared immediate CAG to delayed or no CAG in the setting of cardiac arrest and NSTEMI. The primary outcome was long-term mortality and secondary outcomes included short-term mortality and a Cerebral Performance Category (CPC) score of 1–2 at the longest follow-up period. A random-effects model was used to report odds ratios (ORs) with Bayesian 95% credible intervals (CrIs), and ORs with 95% confidence intervals (CIs) for both network and direct meta-analyses, respectively. Results: 11 studies were included in the final analysis: 8 observational, 1 post-hoc analysis and 2 randomized trials, totaling 3702 patients. The mean age was 63.8 ± 12.8 years with 78% males. We found that immediate and delayed CAG were associated with lower long-term mortality when compared to no CAG (OR 0.21; 95% CrI 0.05–0.82) and (OR 0.11; 95% CrI 0.03–0.43), as well as lower short-term mortality (OR 0.17; 95% CrI 0.04–0.64) and (OR 0.07; 95% CrI 0.01–0.29), respectively. In addition, immediate and delayed CAG were associated with a significantly higher number of patients with a CPC score of 1–2 (OR 4.15; 95% CrI 1.10–16.10) and (OR 4.67; 95% CrI 1.53–15.12), respectively. There were no significant differences between immediate or delayed CAG regarding long-term mortality, short-term mortality, or favorable CPC score. Conclusions: Among patients who survived cardiac arrest with an NSTEMI, CAG is associated with a higher rate of survival and favorable neurological outcomes compared with no CAG. There were no differences between immediate and delayed strategies.